2023
DOI: 10.3390/pharmaceutics15020613
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumor Accumulation of Low-Molecular-Weight Hyaluronic Acid/Chitosan Nanocomplexes for Photothermal Therapy

Abstract: Targeted phototheranostic nanosystems involving both cancer-specific near-infrared (NIR) fluorescence imaging and NIR light-induced phototherapy have shown great potential to improve cancer detection and treatment. In this study, a bifunctional nanocomplex based on low-molecular-weight hyaluronic acid (LMW-HA) and chitosan oligosaccharide lactate (COL) conjugating a zwitterionic NIR dye (ZW800-1) was rationally designed and prepared, and it was simultaneously used to enhance tumor accumulation and photothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…PTT agents should have strong absorption in the traditional near-infrared (NIR) region (650–950 nm) for efficiently converting light energy into thermal energy to induce hyperthermia, leading to cancer cell death [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Although many different types of PTT agents have shown great promise in cancer treatment, the optimization of nanoparticles is still required to overcome the limitations of nanoagent-based PTT, such as low tumor targetability, short tumor retention, poor biocompatibility, potential long-term toxicity, and complicated synthetic processes [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTT agents should have strong absorption in the traditional near-infrared (NIR) region (650–950 nm) for efficiently converting light energy into thermal energy to induce hyperthermia, leading to cancer cell death [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Although many different types of PTT agents have shown great promise in cancer treatment, the optimization of nanoparticles is still required to overcome the limitations of nanoagent-based PTT, such as low tumor targetability, short tumor retention, poor biocompatibility, potential long-term toxicity, and complicated synthetic processes [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among all the phototherapy methodologies, photothermal therapy (PTT), which adopts photothermal agents (PTAs) to convert absorbed photons into hyperthermia, is an attractive tumor treatment modality [ 12 , 13 , 14 , 15 , 16 ]. Numerous studies have demonstrated that photothermal therapy exhibits remarkable efficacy in cancer treatment [ 17 , 18 , 19 ]. Compared to the traditional treatments like radiotherapy and chemotherapy, PTT possesses the superiorities of non-invasiveness, remote controllability, minimal side effects, and insignificant drug resistance [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%